Adobe Photoshop CC for photographers : 2014 release : a professional image editor's guide to the creative use of Photoshop for the Macintosh and PC - Evening, Martin (Routledge, 2014)
Adobe Photoshop for Photographers 2014 Release by Photoshop hall-of-famer and acclaimed digital imaging professional Martin Evening has been fully updated to include detailed instruction for all of the updates to Photoshop CC 2014 on Adobe's Creative Cloud, including significant new features, such as Focus Area selections, enhanced Content-Aware filling, and new Spin and Path blur gallery effects. This guide covers all the tools and techniques photographers and professional image editors need to know when using Photoshop, from workflow guidance to core skills to advanced techniques for professional results. Using clear, succinct instruction and real world examples, this guide is the essential reference for Photoshop users of all levels. Accompanying the book is the photoshopforphotographers.com website, with sample images, tutorial videos, and bonus chapters.